Normative Perceptions of Cannabis Use Among European University Students: Associations of Perceived Peer Use and Peer Attitudes With Personal Use and Attitudes - AKVARDAR, YILDIZ (ALCOHOL RES DOCUMENTATION INC CENT ALCOHOL STUD RUTGERS UNIV, 2016)
Objective: Perceptions of peer behavior and attitudes exert considerable social pressure on young adults to use substances. This study investigated whether European students perceive their peers' cannabis use and approval of cannabis use to be higher than their own personal behaviors and attitudes, and whether estimations of peer use and attitudes are associated with personal use and attitudes. Method: University students (n = 4,131) from Belgium, Denmark, Germany, the Slovak Republic, Spain, Turkey, and the United Kingdom completed an online survey as part of the Social Norms Intervention for Polysubstance usE in students (SNIPE) Project, a feasibility study of a web-based normative feedback intervention for substance use. The survey assessed students' (a) personal substance use and attitudes and (b) perceptions of their peers' cannabis use (descriptive norms) and attitudes (injunctive norms). Results: Although most respondents (92%) did not personally use cannabis in the past 2 months, the majority of students thought that the majority of their peers were using cannabis and that their peers had more permissive attitudes toward cannabis than they did. When we controlled for students' age, sex, study year, and religious beliefs, perceived peer descriptive norms were associated with personal cannabis use (odds ratio [OR] = 1.42; 95% CI [1.22, 1.64]) and perceived injunctive norms were associated with personal attitudes toward cannabis use (OR = 1.46; 95% CI [1.09, 1.94]). Conclusions: European students appear to possess similar discrepancies between personal and perceived peer norms for cannabis use and attitudes as found in North American students. Interventions that address such discrepancies may be effective in reducing cannabis use.
Keywords: SOCIAL NORMS APPROACH; ILLICIT DRUG-USE; MARIJUANA USE; COLLEGE-STUDENTS; HEALTH OUTCOMES; SUBSTANCE USE; ALCOHOL-USE; MISPERCEPTIONS; COUNTRIES; RISK